STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN KUALITAS SEKOLAH MENUJU SEKOLAH UNGGUL - Mas’ati Mas’ati (Guru Membangun, 2023)
Principal leadership is a method used by a principal to realize the ideals of the school he leads. The aim of this research is to describe the leadership strategies implemented by MTs Neg school principals. 2 Kolaka as an effort to improve the quality of its schools towards excellence. The methods used in this research are observation, interviews and documentation. The data obtained is not in numerical form because it is qualitative. The data obtained was then analyzed to see the leadership methods applied by the principal in making his school an excellent school. The results of the research concluded that the principal's leadership strategy in improving quality towards a superior school was carried out by implementing several strategies, including looking at input, processes and supporting documents. Input in relation to the admission of new students, processes relating to the implementation of learning activities, and documents relating to supporting facilities and infrastructure so that all of this is expected to create a superior quality school